The Effectiveness of Annotation Text Strategies to Improve Reading Comprehension Ability In Indonesia - Maria Simatupang; Caroline Victorine Katemba, (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
The purpose of this study is to find out the improvement of students' reading comprehension through Annotation text. They were divided into two class, one class read individually, and the other class read in a group. This study used a quantitative research method and comparative design by using pre-test and post-test. This study was designed to find out the answer to the following question: What is the achievement of the students who are taught using individual annotating text and group annotation text? Is there any significant difference in students' reading comprehension improvement between students who are taught using individual annotation text and students who are taught using group Annotation text? What are the responses of the students after being treated using Annotation text strategy? The instrument used for this study is a reading comprehension test, which contained 28 questions and a questionnaire which contained 10 questions. The result of this study shows that both classes improved in their reading comprehension. In addition, there is a significant difference between those who were taught Annotation text individually and those who were taught Annotation text in the group. This research furthermore showed that there were positive responses concerning the method applied to improve students' reading comprehension.